Estudio de factibilidad para la creación y apertura de un frigorífico para cárnicos en el cantón Pichincha provincia de Manabí, año 2015 - Ganchozo Chávez, Tomás Vinicio (2015)
The purpose of this study was to determine the feasibility of the creation of a refrigerator for meat in the canton, Pichincha, in the province of Manabí, in order to meet the needs of the meat sector of the area. The business idea arises because in the sector there is a place or establishment where you can store and preserve meat products, since in many cases there are drawbacks in the preservation and quality of meat, flaws affecting business development and it has even affect final consumers. A study of market supply and demand of meat products from the region was implemented to determine the viability and profitability of the project's feasibility. Demand 360 people from the canton of Pichincha and offer comprise 19 owners of commercial premises of meat of the sector, samples that were obtained from a population of 34.068, according to projection of the National Institute of statistics and censuses (INEC) in 2015. The market study revealed the tastes, preferences and public acceptance (traders and consumers of meat) objective of the sector, concerning the creation of a refrigerator to store meat in the canton, Pichincha, also gave guidelines to establish the technical, economic and financial study. Technical, economic and financial study revealed that the place where arises to create the refrigerator meets the requirements necessary to build the facilities and meet the needs of demand, also connects to all major highways and roads in the canton. The economic and financial study demonstrates that the project is cost-effective, since there is high demand and projected income for the well-being and development of the new business. The results of this study in this document show the profitability of the same and the important thing would be for the commercial development of the canton of Pichincha. Keywords: business plan, market research, technical studies, economic analysis, financial analysis, feasibility, profitability.